Unlikely allies in the academy : women of color and white women in conversation - Dace, Karen L. (New York, NY : Routledge, 2012)
'Unlikely Allies in the Academy brings the voices of women of Color and White women together for much-overdue conversations about race. These well-known contributors use narrative to expose their stories, which are at times messy and always candid. However, the contributors work through the discomfort, confusion, and frustration in order to have honest conversations about race and racism.The narratives from Chicanas, Indigenous, Asian American, African American, and White women academicians explore our past, present, and future, what separates us, and how to communicate honestly in an effort to become allies. Chapters discuss the need to interrupt and disrupt the norms of interaction and engagement by allowing for the messiness of discomfort in frank discussion. The dialogues model how to engage in difficult dialogues about race and begin to illuminate the unspoken misunderstandings about how White women and women of Color engage one another. This valuable book offers strategies, ideas, and the hope for moving toward true alliances in the academy and to improve race relations. This important resource is for Higher Education administrators and scholars grappling with the intersectionality of race and gender as they work to understand, study, and create more inclusive climates'-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Women in higher education -- United States; Discrimination in higher education -- United States; Sex differences in education -- United States; Intercultural communication -- United States; Cultural pluralism -- United States